N-Doped nanodots/np+-Si photocathodes for efficient photoelectrochemical hydrogen generation. Issue 83 (7th September 2015) - Chen, Deliang; Dai, Song; Su, Xiaodong; Xin, Yu; Zou, Shuai; Wang, Xusheng; Kang, Zhenhui; Shen, Mingrong
Abstract : N2 -plasma treated carbon nanodots are demonstrated to be an effective catalyst for solar-driven H2 production on np + -Si photocathodes. Abstract : Carbon nanodots treated with N2 -plasma are effective catalysts for solar-driven hydrogen-evolved-reaction on np + -Si photocathodes and a support for Pt allowing for the reduction in Pt loading by a factor of about 3.5 while improving the photoelectrochemical activity.